2006
DOI: 10.1007/s10549-006-9198-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of aromatase and 17-β-hydroxysteroid dehydrogenase type 1 mRNA expression in predicting the clinical outcome of human breast cancer

Abstract: Our study shows that higher levels of the enzymes responsible for the local biosynthesis of estrogens especially aromatase are associated with a poor clinical outcome in patients with breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…Because increased aromatase activity results from increased aromatase gene expression, (25,26) we next evaluated the effect of AIs on the levels of mRNA aromatase (CYP19) expression. Formestane alone markedly reduced CYP19 expression (50-60%); the inhibition was greater in the presence of herceptin (85-90%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because increased aromatase activity results from increased aromatase gene expression, (25,26) we next evaluated the effect of AIs on the levels of mRNA aromatase (CYP19) expression. Formestane alone markedly reduced CYP19 expression (50-60%); the inhibition was greater in the presence of herceptin (85-90%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…17 β HSD1 and 17 β HSD2 are involved in the interconversion of E2 with the less potent E1 [33]. Increased 17 β HSD1 expression in breast cancer, either alone or in combination with CYP19, enhances estrogen concentrations and negatively impacts prognosis [50, 51], as does loss of 17 β HSD2 expression [52]. In the present study, the mRNA expression of pro-estrogenic 17 β HSD1 was detected in MCF10A cells but was more abundant in the neoplastic MCF10CA1a and MCF10DCIS.com variants.…”
Section: Discussionmentioning
confidence: 99%
“…This results in an increased level of E 2 that drives the proliferation of the tumour tissue via the ER. Several studies have indicated that patients with tumours that have high 17b-HSD1 expression have significantly shortened disease-free and overall survival (Gunnarsson et al 2005, Salhab et al 2006, Vihko et al 2006, suggesting that compounds which inhibit the activity of this enzyme may be of therapeutic benefit in the treatment of hormone-dependent breast cancer in post-menopausal patients .…”
Section: B-hsd1 Inhibitionmentioning
confidence: 99%